Mechanical and Thermal Evaluation of Carrageenan/Hydroxypropyl Methyl Cellulose Biocomposite Incorporated with Modified Starch Corroborated by Molecular Interaction Recognition - Nur Amalina, Ramli; Fatmawati, Adam; Khairatun Najwa, Mohd Amin; Noor Fitrah, Abu Bakar; Ries, Michael E. (ACS Publication, 2022)
Vegetarian hard capsule has attracted surging demand as an alternative to gelatin; however, only few have been commercialized. Carrageenan extracted from seaweed has the potential to be utilized as a hard capsule material. Improving the mechanical and thermal properties of carrageenan biocomposite is therefore of great importance for future use in the drug delivery system. Hence, carboxymethyl sago starch (CMSS) was incorporated to strengthen the carrageenan biocomposite in a concentration range from 0 to 1.0% w/v. The intermolecular hydrogen bonding formed between carrageenan and CMSS was revealed via density functional theory (DFT) calculations and substantiated by 1H NMR and FTIR spectra. The result showed that the hydrogen bond is established between hydroxyl (carrageenan)–carbonyl (CMSS) groups at a distance of 1.87 Å. The bond formation subsequently increased the tensile strength of the biocomposite film and the loop strength of the hard capsule by 20.6 and 7.7%, respectively. The glass transition temperature of the film was increased from 37.8 to 47.8 °C, increasing the thermal stability. The activation energy upon decomposition of the film is 74.4 kJ·mol–1, representing a 26.2% increase over the control carrageenan. These findings demonstrate that incorporation of CMSS increases the properties of carrageenan biocomposite and provides a promising alternative to animal-based hard capsules.